(untitled) (Al-Qamar, 2023)
Nawab Bahadur Yar Jang was a prominent leader in the freedom movement in the State of Hyderabad, playing a significant role in the socio-political activities of his time. He is remembered for his inspiring speeches, delivered with fiery oratory skills in Urdu, that captured the attention of millions of people at the local and national level. During his 39 years of service to the nation from 1905–1944, he formed socio-political organizations to safeguard the interests of his community, including the State Muslim League, which protected the political rights of Muslims in the state of Hyderabad. Jang not only projected the demands of Muslims through this organization, but also played a pivotal role in carrying the message of the Muslim League to other states. Jang’s dynamic role in generating political awakening and uniting the States Muslims under the platform of the Muslim League was crucial in cultivating social and political consciousness, which paved the way for the creation of Pakistan. This paper focuses on his invaluable services in cultivating the social and political consciousness of States Muslims, bringing success to the Muslim League in the Northwest Front. As far as the methodology of the present study is concerned, it is based on quantitative historical-descriptive approach. Various sources have been consulted for the present study including primary and secondary sources.